The efficiency of oxidative deterioration stabilization of meat-containing products w ith balanced of fatty acid composition - Bozhko, Nataliia; Pasichnyi, Vasyl; Marynin, Andriy; Tyshchenko, Vasyl; Strashynskyi, Igor; Kyselov, Oleksandr (My University, 2020)
Using Peking duck meat in the technology of semi-smoked meat-containing sausage makes it possible to obtain a product with a high content of unsaturated fatty acids, including essential, and the recommended ratios of the ω-3/ω-6 fatty acids. Our study of the RE influence on the course of oxidative processes in a semi-smoked sausage made from Peking duck meat has confirmed the high antioxidant activity of rosemary extract and the effective inhibition of the process of oxidation of lipids in meat-containing sausage products. The rational level of RE concentration has been established, which is effective for inhibiting the oxidative processes in the semi-smoked sausage with Peking duck meat. The largest effect has been obtained when introducing an extract of rosemary in the amount of 0.06 % to the mass of the raw materials, which makes it possible to reduce indicators of the oxidative spoilage of fat by more than twice. Використання пекінського м’яса качки в технології напівкопченої м’ясовмісної ковбаси дозволяє отримати продукт з високим вмістом ненасичених жирних кислот, включаючи незамінні, та рекомендованим співвідношенням жирних кислот ω-3 / ω-6. Наше вивчення впливу РЕ на хід окисних процесів у напівкопченій ковбасі, виготовленій із м’яса пекінської качки, підтвердило високу антиоксидантну активність екстракту розмарину та ефективне гальмування процесу окислення ліпідів у м’ясовмісних ковбасних виробах. Встановлено раціональний рівень концентрації РЕ, який є ефективним для гальмування окисних процесів у напівкопченій ковбасі з м'ясом пекінської качки. Найбільший ефект отримано при введенні екстракту розмарину в кількості 0,06% до маси сировини, що дозволяє зменшити показники окислювального псування жиру більш ніж удвічі.
Keywords: meat-containing semi-smoked sausage; duck meat; unsaturated fatty acids; rosemary extract; напівкопчена м’ясомістка ковбаса; м’ясо качки; ненасичені жирні кислоти; екстракт розмарину; кафедра технології м’яса і м’ясних продуктів; ‎кафедра технологічного обладнання та комп′ютерних технологій проектування‎